Factors influencing the induction of immune responses with DNA vaccines - Daly, Lyn M. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2002)
Compared with any other medical discovery vaccines have prevented more deaths and suffering. Emergence of novel pathogens accentuates the requisite for ongoing development and improvement of traditional vaccination strategies. Understanding the role of T helper cells in regulation of the immune response is imperative for manipulation of the host immune response and in the design of novel vaccines. Concerns regarding safety and poor immunogenicity of conventional vaccines has provoked the development of safer more immunogenic vaccines, such as those based on naked DNA. Injection of plasmid DNA coding for the protective antigen of a pathogen can generate antigen-specific cellular and humoral responses. Immunogenicity of protein and DNA vaccines may be influenced by several factors, including route of administration, dose, immunization schedule, type of antigen and presence of an adjuvant. This project focuses on characterizing the immune responses induced by plasmid DNA encoding the gp120 surface glycoprotein of HIV-1 virus and the transmembrane hemagglutinin protein of influenza virus. Induction of virus-specific CD4+ Th1 and CD8+ CTLs are recognized as ideal objectives in the design of many viral vaccines. Modulation of the immune response induced with gp120pDNA towards a Th1-type profile was achieved by co-administration of plasmids coding for IL-12 cytokine and cationic liposomes. The use of prime/boost immunization schedule demonstrated that priming with gpl20pDNA followed by a gp120-alum could augment type-1 responses. Multivalent vaccines are possible with DNA vaccine technology and this study found that responses to individual plasmids were not adversely affected by the presence of supplementary plasmids. This study also demonstrated that encoded antigen and plasmid composition influenced the induction of immune responses. Encoding gp120 protein in distinct bacterial plasmid backbones augmented gp120-type-1 responses, emphasizing the importance of selecting an appropriate plasmid backbone depending on the target pathogen. Collectively these findings indicate that many factors influence the induction of immune responses with DNA vaccines. Knockout mice were used to demonstrate the importance of IL-4, IL-10 and IL-12 in directing the response, which appeared to be independent of antigen-type. HIV gp120 protein encoded by plasmid DNA was found to influence BMDC maturation, chemokine and cytokine production. HA-primed APC were detected in secondary lymphoid organs following immunization with HApDNA. Furthermore, in vitro HApDNA-stimulated BMDC activated a HA-specific Th1 clone to secrete type-1 cytokines, establishing a key role for DC in the induction of immune responses with DNA vaccines. This study has identified several factors that influence the immunogenicity of DNA vaccines. Exploring the dynamics of this technology will allow a more logical approach to designing effective novel vaccines. DNA vaccines represent a safe, immunogenic, inexpensive and rapid means of generating immunity against several pathogens and may contribute to eradicating the devastation caused by HIV and many other infectious microorganisms.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin